(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
Big data technologies enable cities to develop towards a smart city. However, the adoption of big data technologies is challenging, which is why it is essential to identify factors that influence the adoption of big data technologies in cities. The main goal of the paper is to propose a conceptual model of big data technologies adoption in smart cities of the European Union. In order to derive the conceptual model following is done: i) overview of the previous Technology-OrganisationEnvironment framework - based research on the adoption of selected information and communications technologies crucial for the development of smart cities, and ii) selection of factors based on the critical examination of the previous research. Selected factors, Absorptive Capacity, Technology Readiness, Compatibility, City Managements Support, the Existence of Smart City Strategy and Stakeholders Support, were incorporated into the conceptual model of big data technologies adoption in smart cities of the European Union. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.